Development of collagen/polydopamine complexed matrix as mechanically enhanced and highly biocompatible semi-natural tissue engineering scaffold. (1st January 2017) - Hu, Yang; Dan, Weihua; Xiong, Shanbai; Kang, Yang; Dhinakar, Arvind; Wu, Jun; Gu, Zhipeng
Graphical abstract: Abstract: To improve the mechanical properties and biocompatibility of collagen I matrix, a novel and facile strategy was developed to modify porcine acellular dermal matrix (PADM) via dopamine self-polymerization followed by collagen immobilization to enhance the biological, mechanical and physicochemical properties of PADM. Mechanism study indicated that the polymerization of dopamine onto PADM surface could be regulated by controlling the amount of hydrogen bonds forming between phenol hydroxyl (COH) and nitrogen atom (NCO) within collagen fibers of PADM. The investigations of surface interactions between PDA and PADM illustrated that PDA-PADM system yielded better mechanical properties, thermal stability, surface hydrophilicity and the structural integrity of PADM was maintained after dopamine coating. Furthermore, collagen (COL) was immobilized onto the fresh PDA-PADM to fabricate the collagen-PDA-PADM (COL-PDA-PADM) complexed scaffold. The MTT assay and CLSM observation showed that COL-PDA-PADM had better biocompatibility and higher cellular attachment than pure PADM and COL-PADM without dopamine coating, thus demonstrating the efficacy of PDA as the intermediate layer. Meanwhile, the expression of basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) of COL-PDA-PADM were investigated by an in vivo study. The results revealed that COL-PDA-PADM could effectively promote bFGF and VEGF expression, possibly leading to enhancing the dura repairing process. Overall, this work contributed a new insight into the development of a semi-natural tissue engineering scaffold with high biocompatibility and good mechanical properties. Statement of Significance: Obtaining scaffolds with high biocompatibility and good mechanical properties is still one of the most challenging issues in tissue engineering. To have excellent in vitro and in vivo performance, scaffolds are desired to have similar mechanical and biological properties as the natural extracellular matrix, such as collagen based matrix. Utilizing the surface self-crosslinking and coating strategy, we successfully obtained a novel semi-natural platform with excellent biological and mechanical properties from porcine acellular dermal matrix (PADM), polydopamine and collagen. The results confirmed that this scaffold platform has very excellent cellular performance and very little toxicity/side effects in vivo . Therefore, this semi-natural scaffold may be an appropriate platform for tissue engineering and this strategy would further help to develop more robust scaffolds.